تقرير الاحتياجات المائية لمحصول الطماطة في قضاء الزبير - الحمادة، منعم مجيد حمد (جامعة البصرة - كلية الآداب, 2010)
تمثل دراسة الاحتياجات المائية للمحاصيل الزراعية أهمية بالغة لاسيما في المناطق الجافة وشبه الجافة ذات الموارد المائية المحدودة كما هو الحال في منطقة الزبير لكونها تساعد على تحديد كمية مياه الري والمساحة التي يمكن ريها كما تساعد على اختيار طريقة الري المشكل في تلك المناطق لتقليل الضائعات المائية والاستفادة العقلانية من مصادر المياه المتوفرة فيها ولهذا فأن هذه الدراسة تهدف إلى تحليل العوامل المؤثرة في الاحتياجات المائية لمحصول الطماطة في قضاء الزبير وتقدير كمية تلك الاحتياجات خلال مراحل نمو المحصول ومقارنتها مع التجهيز المائي الفعلي وتحديد طريقة الري المثلى التي تستهلك كمية اقل من مياه الري. \ وقد تبين من الدراسة إن هناك مجموعة من العوامل تؤثر في الاحتياجات المائية لمحصول الطماطة في منطقة الدراسة تمثلت بالظروف المناخية التي تتميز بقلة الأمطار وارتفاع درجات الحرارة وشدة التبخر التي نجم عنها زيادة الاحتياجات المائية النظرية فضلا عن طبيعة تربة قضاء الزبير ذات الأنسجة الخشنة والنفإذية العالية التي ساهمت في زيادة الضائعات المائية عن طريق التسرب والغور العميق وبالتالي زيادة الاحتياجات المائية الكلية للمحصول. \ كما إن لطول موسم نمو محصول الطماطة الذي يستغرق (273) يوما تأثير واضح في زيادة الاحتياجات المائية كما إن لطريقة الري المشبعة دور كبير في حجم الضائعات المائية حيث تبين من الدراسة إن كمية التجهيز المائي الفعلي تحت طريقة الري بالتنقيط تشكل نسبة مقدارها (9.8%) من مثيلتها تحت طريقة الري بالمروز وان هناك توافق بين الاحتياجات المائية ومتطلبات الغسل النظرية وبين كمية التجهيز المائي الفعلي لمحصول الطماطة باستخدام طريقة الري بالتنقيط في حين لا يوجد توافق بينهما في حالة استخدام طريقة الري بالمروز. \ وقد بينت الدراسة كذلك إن الاحتياجات المائية الكلية (المقننات المائية) لمحصول الطماطة خلال موسم النمو بلغت (3332.6 متر مكعب / دونم) وتختلف من مرحلة إلى أخرى تبعا لاختلاف درجات الحرارة وتساقط الأمطار وشدة التبخر ووجود الغيوم واختلاف مراحل نمو المحصول. A study of water needs of crops crucial, especially in arid and semi-arid with limited water resources, as is the case in the Zubayr area, they help determine the amount of irrigation water and space that can be irrigated and are helping to choose the method of irrigation problem in those areas to reduce Losses water use rationality sources of water available which is why this study aims to analyze factors affecting the water needs of the crop tomatoes in Zubair and quantify those needs through the stages of crop growth and compare it with the installation of water effective and determine the method of irrigation best that consume the least amount of irrigation water. \ The study found that there are a variety of factors affect the water needs of the crop tomatoes in the study area was climatic conditions characterized by low rainfall and high temperatures and the intensity of evaporation, which resulted in increasing demand for water theory as well as the nature of the soil Zubair with tissue coarse and high permeability, which contributed losses increase in water through leakage and deep valley and thereby increase the total water needs of the crop. \ The length of the growing season and harvest tomatoes, which takes (273) days clear impact on the increasing demand for water is also the method of irrigation saturated significant role in the size of losses water where the study found that the amount of processing water under a virtually drip irrigation system accounted for the amount (9.8%) than that under the irrigation method Channels and there is a consensus between the needs and requirements of water washing between the theoretical and the actual amount of water for processing tomato crop using drip irrigation method in a while does not agree between them in the case of the use of irrigation method Channels \ The study showed further that the water needs of the college (the associated water) to harvest tomatoes during the growing season was (3332.6 cubic meters / acres) and varies from one phase to another depending on the different temperatures, rainfall and the intensity of evaporation and the presence of clouds and the different stages of crop growth
Keywords: قضاء الزبير -- العراق -- المحاصيل الزراعية -- الإنتاج الزراعي -- الطماطم -- زراعة الطماطم